Spent coffee grounds biochar from torrefaction as a potential adsorbent for spilled diesel oil recovery and as an alternative fuel. (15th January 2022) - Lee, Kuan-Ting; Cheng, Ching-Lin; Lee, Da-Sheng; Chen, Wei-Hsin; Vo, Dai-Viet N.; Ding, Lu; Lam, Su Shiung
Abstract: A new approach using torrefied spent coffee grounds (TSCG) as a bioadsorbent is presented for marine oil spill recovery. The adsorbent after diesel adsorption is referred to as "oilchar". The torrefaction of spent coffee grounds (SCG) is performed at 200, 250, and 300 °C where the solid yields are 95%, 80%, and 62%, respectively. The specific surface area, hydrophobicity, thermal stability, diesel adsorption capacity of SCG increases with increasing torrefaction temperature. SCG torrefied at 300 °C (300-TSCG) can intensify its specific surface area, contact angle, crystallinity, diesel adsorption capacity by factors of 7.6 folds, 10.3%, 35%, and 1.47 times, respectively. The diesel adsorption capacity of 300-TSCG is 1.36 times that of commercial activated carbon. The higher heating value of 300-TSCG is 30.32 MJ kg −1, accounting for a 45.1% improvement compared with that of untorrefied SCG. After adsorbing diesel, the HHV of the oilchar from 300-TSCG is 1.23 times that of SCG-oilchar, while the ignition temperature of 300-TSCG decreases from 301 to 157 °C. Overall, TSCG is a promising material to adsorb spilled diesel oil for environmental protection, and the resultant oilchar is a potential alternative fuel for thermal power plants and steel mills, thereby achieving waste reuse and circular economy. Graphical abstract: Image 1 Highlights: TSCG adsorbent is used as a new approach of oil spill recovery. Specific surface area of 300-TSCG is 7.6 times higher than that of untorrefied SCG. Diesel adsorption capacity of 300-TSCG is 1.47 times that of untorrefied SCG and 1.36 times that of AC. HHV of 300-Oilchar is 39.78 MJ kg −1, which is 1.23 times that of SCG-Oilchar. After adsorbing diesel, 300-TSCG ignition temperature decreases from 301 °C to 157 °C.